Jaringan Ilmu Nusantara-Timur Tengah Dan Peran Pesantren Dalam Jaringan-Nya - Muhammad Isa Anshori; Ikke Fitriana Nugrahini; Aulia Arsinta (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
The intellectual network between the Indonesian Archipelago and the Middle East has existed since the early centuries of Islam and has played an important role in the development of Islamic scholarship in the Southeast Asian region. This study aims to examine the dynamics of the scientific relationship between Indonesian and Middle Eastern scholars and to trace the contribution of Islamic boarding schools as traditional Islamic educational institutions in building and strengthening this network. Using a qualitative approach and literature study of manuscripts, biographies of scholars, and classical works, this study found that Islamic boarding schools have a strategic role as centers for the transmission of knowledge, preservers of scientific traditions, and liaisons between local students and centers of knowledge in the Middle East, such as Mecca, Medina, and Cairo. Through the departure of students to the Middle East and the arrival of scholars to the Indonesian Archipelago, there was an exchange of ideas, teaching methods, and the development of contextual Islamic thought. The role of Islamic boarding schools in this network is not only limited to the educational aspect, but also forms a strong, moderate, and traditional local Islamic identity. This finding emphasizes the importance of Islamic boarding schools in maintaining the continuity of global Islamic knowledge while maintaining local wisdom within the framework of Islamic civilization. Abstrak Jaringan intelektual antara Nusantara dan Timur Tengah telah berlangsung sejak abad-abad awal kedatangan Islam dan memainkan peran penting dalam perkembangan keilmuan Islam di kawasan Asia Tenggara. Penelitian ini bertujuan untuk mengkaji dinamika hubungan keilmuan antara ulama Nusantara dan Timur Tengah serta menelusuri kontribusi pesantren sebagai institusi pendidikan Islam tradisional dalam membangun dan memperkuat jaringan tersebut. Dengan pendekatan kualitatif dan studi pustaka terhadap manuskrip, biografi ulama, serta karya-karya klasik, penelitian ini menemukan bahwa pesantren memiliki peran strategis sebagai pusat transmisi ilmu, pelestari tradisi keilmuan, dan penghubung antara pelajar lokal dengan pusat-pusat ilmu di Timur Tengah, seperti Mekkah, Madinah, dan Kairo. Melalui keberangkatan santri ke Timur Tengah dan kedatangan ulama ke Nusantara, terjadi pertukaran ide, metode pengajaran, serta pengembangan pemikiran keislaman yang kontekstual. Peran pesantren dalam jaringan ini tidak hanya terbatas pada aspek pendidikan, tetapi juga membentuk identitas keislaman lokal yang kuat, moderat, dan berakar pada tradisi. Temuan ini menegaskan pentingnya pesantren dalam mempertahankan kesinambungan keilmuan Islam global sekaligus merawat kearifan lokal dalam bingkai peradaban Islam.